Bacillus biofilm formation and niche adaptation shape long-distance transported dust microbial community - Lang-Yona, Naama; Lahav, Ella; Levy Barazany, Hilit; Salti, Talal; Rahamim- Ben Navi, Liat; Murugan, Prem Anand; Kolodkin-Gal, Ilana (Communications earth & environment, 2025)
Long-distance microbial transport via dust events is projected to intensify globally. However, survival mechanisms of air- and dust-borne bacteria and their contribution to global processes remain poorly understood. In this study, we characterized Bacillus species from transitional season dust storms, previously identified as a significant component of the bioactive community of the dust microbiome. Our results demonstrated substantial growth and surface-associated biofilm formation diversification, linked to niche adaptation within heterogeneous dust particles. Most dust isolates formed biofilms while showing varying preferences for media composition under standard laboratory conditions, extreme temperatures, and low humidity. Sterile dust stimulated biofilm formation, growth, and matrix gene expression of B. subtilis , leading to robust biofilm development in key related dust isolates. This effect surpassed that of inorganic, synthetic dust, representing a role for organic substrates from decayed dust-community members. Overall, these findings offer direct evidence that biofilm formation serves as an adaptive mechanism in the unique habitat of dust particles, suggesting that niche adaptation may play a role in microbial survival across dust storms. These results hold significant implications for terrestrial and aquatic ecology and health, suggesting a pivotal process by which bacteria survive and evolve in this understudied habitat. Bacillus forms airborne biofilms as an adaptive mechanism to survive transport in dust storms, according to analysis of airborne dust storm samples.